Online Peer Observation: Research and Practice - Bowskill, Nick; Brock, Susan; Mavrommati, Maria (Proceedings of the International Conference on Networked Learning, 2018)
Online peer observation is an emerging field which remains under-researched. It offers opportunities for part-time and associate lecturers to join in the life of the institution and overcome the potential for social isolation. It can be approached by individuals in many different ways, with many different outcomes. This workshop will present a model which will equip participants to make crucial decisions about their own institutional, or individual, peer observation practices. This workshop provides a new model of Teaching Observation with which to explore relevant issues and opportunities with fellow participants. At the same time, the facilitators will share the development of their practice, via online peer observation at University of Derby Online (Bowskill et al., 2017).